2021
DOI: 10.21203/rs.3.rs-158094/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of zero-valent iron/biochar by carbothermal reduction from wood waste and iron mud for removing rhodamine B

Abstract: This study proposes a new process to synthesize zero-valent iron/biochar (Fe0-BC) by carbothermal reduction using wood waste and iron mud as raw materials under different temperature. The characterization results showed that the Fe0-BC synthesized at 1200ºC (Fe0-BC-1200) possessed favorable adsorption capacity with the specific surface area of 103.18 m2/g, and that the zero-valent iron (Fe0) particles were uniformly dispersed on the biochar surface. The removal efficiency of rhodamine B (RB) was determined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…5 b. The weakened –OH vibration at 3432 cm −1 demonstrated that the functional groups were involved in the Cr(VI) removal, which could be reduction or formation of complexations 46 . The same phenomena were observed for the C=C and C–O stretching, indicating the different functional groups contributed to the Cr(VI) removal.…”
Section: Resultsmentioning
confidence: 97%
“…5 b. The weakened –OH vibration at 3432 cm −1 demonstrated that the functional groups were involved in the Cr(VI) removal, which could be reduction or formation of complexations 46 . The same phenomena were observed for the C=C and C–O stretching, indicating the different functional groups contributed to the Cr(VI) removal.…”
Section: Resultsmentioning
confidence: 97%